A critical introduction to coaching & mentoring : debates, dialogues & discourses - Gray, David E. (David Edward), 1952-; Garvey, Bob; Lane, David A., 1947- (Los Angeles ; London : Sage, 2016)
"This is the definitive introduction to coaching and mentoring, written by an experienced and multidisciplinary team. Taking you all the way through from the emerging theory to informed practice, the book covers: Skills, purposes and outcomes of coaching and mentoring processes, the many settings in which they take place--public, private and voluntary, coaching and mentoring's evidence base and how it is assessed, [and] the professionalization of coaching and mentoring and a move towards integration. Supported by a wide range of case studies, activities, further questions and topics for discussion, this book is a comprehensive but accessible introduction. The authors take a critical approach and go beyond the basics, to support your development as a critically reflective practitioner"--Publisher's website.
Why coaching and mentoring? Why now? -- Psychology as a perspective to inform our work in coaching and mentoring -- Coaching and mentoring process -- Competence and performance for coaching and mentoring : a contested discourse -- Coaching and mentoring in the learning mix -- Evaluating coaching and mentoring -- Coaching and mentoring in specific contexts -- Leadership, management, coaching and mentoring -- Towards a coaching and mentoring culture -- Introducing coaching and mentoring into an organisation -- Towards a model of coaching supervision -- Professionalisation and ethics -- Research in coaching and mentoring -- Coaching and mentoring and the future.
Includes bibliographical references (pages 311-341) and index.
Keywords: Employees -- Coaching of; Mentoring in business; Employees -- Coaching of